HISTORICAL AND SOCIO-PSYCHOLOGICAL ASPECTS IN THE TRANSLATION OF THE NAUGHTY BOY - Kasimova Ra’no Rakhmatullayevna,; Ikromova Makhliyo, (TADQIQOTLAR, 2026)
Abstract. The article analyzes historical and socio-psychological aspects in the English translation of Gafur Gulam’s “Shum Bola” - “The Naughty Boy.” Attention is given to how the text reflects early twentieth-century Tashkent, poverty, street life, family pressure, and the inner world of the child narrator. The article also studies how these layers are transferred into English and where losses can be seen. A comparative textual method, close reading, and contextual analysis are used. Short extracts from the story and from published translation studies are examined. The analysis shows that the English translation keeps the main plot, humor, and movement of the story, but some culturally marked words, emotional tones, and social details become weaker. Better results can be reached when literal translation is supported by explanation, cultural comment, and careful attention to character speech. The article may be useful for research on literary translation, Uzbek prose, and child-centered narrative.